2015
DOI: 10.1007/s13277-015-3239-z
|View full text |Cite
|
Sign up to set email alerts
|

Death receptor 4 variants enhanced prostate cancer risk in North Indian population

Abstract: Death receptor 4 (DR4) is a tumor suppressor gene and plays an important mediator of apoptosis. Polymorphism in DR4 gene may reduce apoptotic capacity and provoke proliferation of cell and cancer. We evaluated genetic polymorphisms of DR4 gene in association with risk of prostate cancer (PCa) in Northern Indian population. We have recruited 192 PCa patients and 225 cancer-free ages matched unrelated healthy control of similar ethnicity. They were genotyped for DR4, 141 (G > A), 209 (C > G), and 228 (A > C) pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that the SNPs in the DR4 gene are associated with different types of cancers, such as colorectal cancer, 13 prostate cancer, 14 ovarian cancer, 15 lung cancer and head and neck cancer. 16 To the best of our knowledge, the findings reported herein establish for the first-time decreased risk and increased survival times in colorectal cancer patients carrying the rs13278062 GT/TT genotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that the SNPs in the DR4 gene are associated with different types of cancers, such as colorectal cancer, 13 prostate cancer, 14 ovarian cancer, 15 lung cancer and head and neck cancer. 16 To the best of our knowledge, the findings reported herein establish for the first-time decreased risk and increased survival times in colorectal cancer patients carrying the rs13278062 GT/TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Death receptor 4(DR4) contains a cytoplasmic death domain that activates apoptosis by interacting with tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) through the extrinsic death receptor pathway. 12 Several functional single nucleotide polymorphisms (SNPs) in the DR4 gene are associated with different types of diseases, such as colorectal cancer, 13 prostate cancer, 14 ovarian cancer, 15 lung cancer and head and neck cancer, 16 However, the minor allele frequency (MAF) of these SNPs was low in Han Chinese individuals from Beijing, China (CHB populations), suggesting that other variants in DR4 might play an important role in the development of cancer. 11 Furthermore, it has been reported that abnormal expression of DR4 was also correlated with the prognosis of colorectal cancer 10 and lung squamous cell carcinoma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant association was reported for two SNPs of tumor suppressor gene P53 by Mittal et al 2011; with the heterozygous GA genotype of intron-6 polymorphism rs1625895, c.13494G>A (P value=0.051, OR=1.48, 95%CI=0.999-2.220) and heterozygous GC genotype of exon-4 non-synonymous polymorphism rs1042522 (c.215G>C; Arg72Pro) (P value=0.050, OR=1.5, 95%CI=1-2.199) showed an increased risk of PCa [54]. The team also reported 2 missense variants of DR4, rs6557634 (G>A; His141Arg) and rs4871857 (C>G; Thr209Arg) whose homozygous variant genotypes conferred higher PCa risk (P value=0.007, OR(95%CI)=2.54(1.29-5.00) and P value=0.003, OR(95%CI)=2.58 (1.38-4.81), respectively) [55].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 92%